Cardiovascular Risk Associated With Gender Affirming Hormone Therapy in Transgender Population - Aranda, Gloria; Halperin, Irene; Gomez-Gil, Esther; Hanzu, Felicia A.; Seguí, Núria; Guillamon, Antonio; Mora, Mireia (Frontiers in Endocrinology, 2021)
Transgender men and women represent about 0.6 -1.1%% of the general population. Gender affirming hormone therapy (GAHT) helps ameliorate gender dysphoria and promote well-being. However, these treatments' cardiovascular (CV) effects are difficult to evaluate due to the limited number of extensive longitudinal studies focused on CV outcomes in this population. Furthermore, these studies are mainly observational and difficult to interpret due to a variety of hormone regimens and observation periods, together with possible bias by confounding factors (comorbidities, estrogen types, smoking, alcohol abuse, HIV infection). In addition, the introduction of GAHT at increasingly earlier ages, even before the full development of the secondary sexual characteristics, could lead to long-term changes in CV risk compared to current data. This review examines the impact of GAHT in the transgender population on CV outcomes and surrogate markers of CV health. Furthermore, we review available data on changes in DNA methylation or RNA transcription induced by GAHT that may translate into changes in metabolic parameters that could increase CV risk.